An Experiment to Measure the Performance of Phonetic Key Compression Retrieval Schemes - Greenfield, R. H. (Methods of Information in Medicine, 1977)
The results of an experiment to measure the performance of the Davidson and Soundex phonetic key compression schemes in finding sets of records representing the same individual in a moderately large radiology patient file, as compared to exact surname matches, are presented. This is similar to the problem of retrieving a record by name under the assumption that neither the search key nor the recorded key is accurately known. Both phonetic schemes perform similarly in obtaining extra matches and both outperform by a large margin the exact, name match. The results also indicate that the Davidson scheme is superior to the Soundex because it produces significantly fewer mismatches.
Keywords: Name Retrieval Schemes; Phonetic Key Compression; Index Performance; Patient Name Indexes; Davidson Consonant Code; Soundex Code; Record Linkage